Q: What is the answer to -3p plus 6p?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

3p+52

14p + 14q + p - 7q - 6p = 9p + 7q

4p+2 = 3p-7 4p-3p = -7-2 p = -9

p+2 = 2-3p p+3p = 2-2 4p = 0 p = 0

Related questions

3p + 6p = (3 + 6)p = 9p

-9p + 6p = -3p

6p divide by 3p = 2

If: 6p-2-3p = 16 Then: p = 6

None because without an equality sign it is not an equation but it can be simplified to 3p^2 +6p

6p/4 equivalent to = 3p/2

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

The length of BAC in a circle P where BC is 24ft is 3p and not 6p 12p or 24p.

First get all the p variables on one side of the equation by subtracting 6p from both sides. Giving you 3p + 14 = 23 Now subtract 14 from both sides. 3p = 9 Finally divide both sides by 3. p = 3

Factor x2 plus 12xp plus 36p2 is (x+6p)(x+6p).

Expanding and Grouping! 6(p-7) - 5p + 15 + 3p + 2(4) = ?? 6p - 42 - 5p + 15 + 3p + 8 = ?? 6p - 5p + 3p = 42 - 8 - 15 (Remember, what you do to one side, you do to the other. To get rid of -42, you have to add 42 on each side. To get rid of +8, you have to subtract 8 on each side, and so on.) 4p = 19 p = 4.75 Tadah! I love math, So much better than english.

3pq - 6p2 = 3p*(q - 2p)